Combined Testing Approach to Evaluate the Antifungal Efficiency of Clove (Eugenia caryophyllata) Essential Oil for Potential Application in Wood Conservation - POP Dana Mihaela; TIMAR Maria Cristina; BELDEAN Emanuela Carmen; VARODI Anca Maria (BioResources, 2020)
The efficiency of clove (Eugenia carryophyllata) essential oil (C-EO) for the curative antifungal treatment of historic wood was investigated in comparison with two classical biocide products: a boron-based preservative (Diffusit S) and a formulation containing quaternary ammonium salts and isothiazole (Biotin T). A combined approach was adopted that consisted of implementation of C-EO in a practical case study on a degraded beech (Fagus sylvatica) wood artifact and evaluation of the treatment efficacy via an original laboratory mycological test. Small samples, extracted from the degraded wood material before and after curative treatments, were placed as inoculum on sterile culture medium and incubated for periodic monitoring of the emerging fungal growth for 140 d. Direct observation was supplemented with digital quantification of the fungal coverage area via ImageJ software and calculation of the absolute and relative indices of fungal development reduction. The results indicated that the C-EO solutions at both tested concentrations (10%, 5%) were more efficient than the considered reference products at similar concentrations (Diffusit S (10%) and Biotin T (5%)) for curative antifungal treatment. However, none of the treatments applied entirely prevented reactivation of the severe and complex fungal attack, which was highlighted by the mycological tests conducted on the control samples.
Keywords: Essential oils; Historic wood; Curative treatment; Antifungal; Mycological test; ImageJ